Effects of temperature and frequency on the dielectric properties of thiophene compounds and its application in coal microwave-assisted desulfurization. (1st October 2021) - Ge, Tao; Cai, Chuanchuan; Min, Fanfei; Zhang, Mingxu
Highlights: This study provides new insights into the removal mechanism of thiophene in coal at different temperatures and frequencies. This study establishes the relationship between the dielectric properties of organic sulfur components and the desulfurization efficiency. Such knowledge can be used for predicting the removal difficulty of different organic sulfur components in coal with microwave, adjusting and optimizing the process conditions, and provides a new strategy for the industrial application of microwave desulfurization. Abstract: This study aimed to clarify the influence of medium composition, microwave frequency, and temperature on the dielectric properties and desulfurization rates of thiophene components in coal. Thiophene compounds with different structures were selected, and the dielectric parameters at different frequencies and temperatures were investigated. The coal-like substance samples loaded with benzothiophene were prepared and subjected to 915 and 2450 MHz microwave-assisted citric-acid desulfurization at different temperatures. Using X-ray absorption near-edge structure (XANES), changes of organic sulfur components structures and contents in coal-like substances after microwave desulfurization were observed. Results showed that thiophene compounds containing a conjugated structure had poor dielectric properties. The dielectric loss of benzothiophene at 915 MHz was better than that at 2450 MHz. In the temperature range of 20–100 °C, the dielectric loss of benzothiophene increased with the increasing temperature, and both peaked at 90 °C. With the further increase of temperature, the microwave absorbing capacity of benzothiophene decreases. Microwave-assisted citric acid can oxidize part of the benzothiophene in coal-like substances into phenethyl alcohol, sulfoxide, sulfone, sulfonate, sulfite and sulfate. Phenyl alcohol, sulfonate, sulfite and sulfate can be removed by washing with water to remove benzothiophene from coal-like substances. The desulfurization rate was directly related to the dielectric loss of benzothiophene, and the desulfurization rate was highest when the dielectric loss was the largest. When the reaction temperature was 90 °C, 915 MHz frequency microwave radiation citric acid can obtain the best desulfurization effect of benzothiophene in coal-like substances, and the desulfurization rate reached 42.87%.